CONTINGENCY PLAN FOR STRONG RAINS AND FLOODS FOR THE CITY OF PUYO, PASTAZA CANTON, ECUADOR - Barreno-Rojas, Willian Israel (2017)
All contingency plans aim to allow the operation of institutions, even when some of its functions come to a halt because of some incident, either internal or external to the organization. Th e objective of this investigation consisted on establishing the precise and opportune actions for a contingency plan that will allow reducing the vulnerability state and risks before heavy rains and fl oods for the inhabitants of the city of Puyo. Th e investigation was carried out in fi ve places inside the city Puyo, canton Pastaza (Dike of Fatima, Neighborhood Worker-Tideland Citayacu, Sector the Island, Sector Union Bases and Neighborhood Paradise River Big Pindo), Ecuador. Th e climatic variables, temperature and precipitation, as well as the geologic and demographic characteristics of the canton and the time of evacuation were taken into consideration. A contingency plan was elaborated that contemplated the inhabitants of the canton, with higher risks and vulnerability, being focused in the children, pregnant women and seniors, where organizations and state and private entities were involved, to better face the natural disasters, among those entities stand out: Fire department, Red Cross, homes and senior centers, public dining halls and rehabilitation clinics. Th e development of a signage proposal to highlight the areas of higher fl ood danger. We conclude that the proposal of a contingency plan for the city of Puyo is pertinent and necessary, due to the evidence of marked fl oods that aff ect the entire canton of Pastaza.